Scholars’ Views About Taqdīm and Ta’ḵīr in Qur’anic Syllables An Analytical Discourse Study - Dr. Habibullah Khan; Dr. Muhammad Ayub Rasheedi (jihat-ul-islam, 2020)
Qur’an remains the source of dynamic researches in this world at all times. Many scholars belonging to different sects of mind, religion, faith and creed have formally made multidimensional researches related to this Holy Text. They, from their own opinions, extracted a lot of results from this Text while criticizing others’ opinions in this context. The major rhetorical point in this regard is about ‘Saj’: functioning ability, loyalty and constancy. Many scholars consider ‘Saj’ rational in Holy Qur’an rather than irrational. Keeping this point in view they proclaimed that ‘Saj’ as itsel in Qur’an was considered without binding it to the meanings. They extended this point to two other major qualities of Qur’anic Rhetoric; ‘Al-Taqdīm’ and ‘AlTa’ḵīr’. They, most of time, said that ‘Saj’ was basically resulted from ‘Taqdīm’ and ‘Ta’ḵīr’ which had been used to celebrate just words uttering beauty and nothing more. In contrast to it, ‘Taqdīm’ and ‘Ta’ḵīr’ both have principled relation to the words’ meanings and meanings of meanings. The following article shall discuss the forehead issue in detail along with right criticism of the scenario.